Rosai-Dorfman disease: a rare presentation with para-aortic and mesenteric lymphadenopathy, hepatosplenomegaly and ascites - Mohammad Hossein Anbardar; Samaneh Hamzehloo; Fatemeh Fazeli; Soheila Zareifar; Mohammad Hadi Imanieh; Mohammadhossein Bahmanzadegan Jahromi; Amir Mohammad Ghorbani (BMC, 2020)
Abstract Background Rosai-Dorfman disease (RDD) is a rare but well-defined, histiocytic proliferative disorder with massive lymphadenopathy. Case presentation Herein we present the case of a 22-month-old girl with abdominal, neutrophilia, anemia, ascites, hepatosplenomegaly and fever. There were multiple enlarged mesenteric and para-aortic lymph nodes on abdominal ultrasonography and computer tomography scan. Microscopic examination of mesenteric lymph nodes showed dilation of the lymph sinuses occupied by lymphocytes, plasma cells, and many histiocytes. These histiocytes showed emperipolesis within their cytoplasm. With the diagnosis of RDD, prednisolone was started and good response was seen. However, splenomegaly and pancytopenia presented at follow up, and, after several hospital admissions, she died of sepsis. Conclusions RDD should be considered in the differential diagnosis of pediatric lymphadenomegaly. Although most patients experience favorable prognosis, some fatalities occur due to progression and dissemination of the disease.